PILOT-SCALE INVESTIGATION OF AERATION RATE EFFECT ON LEACHATE CHARACTERISTICS IN LANDFILLS - Sekman, Elif; Top, Selin; Varank, Gamze; Bilgili, Mehmet Sinan (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2011)
There is a wide range of aeration rates used in pilot and full-scale aerobic landfill studies in the literature, and the main result of all of these studies is that aeration shortens the stabilization time of the landfill. The main aim of this research was to investigate the effect of aeration rate on solid waste decomposition in aerobic, leachate-recirculated landfills. For this purpose, one anaerobic (R1) and four aerobic reactors (R2, R3, R4 and R5) with aeration rates of 0.1; 0.3; 0.6 and 1.0 L/min kg, respectively, were constructed, and operated with leachate recirculation for 150 days. Leachate quality was monitored by measuring pH, total alkalinity, chemical oxygen demand, biological oxygen demand, chloride, total Kjeldahl nitrogen and ammonia nitrogen parameters. Volume and mass losses in the reactors, as a result of decomposition of solid wastes, were also identified. Based on the analysis of leachate composition and solid waste settlement, no significant effect of the aeration rate was observed on the variations of pH, chloride, alkalinity, COD, BOD5, TKN, and NH3-N parameters with the aeration rates used in this study. The results of the paper show that aeration accelerates the waste stabilization rate in landfilling, and the lowest aeration rate (0.10 L/min kg waste) was the most viable one because of economical reasons. Further studies should be extended to determine the optimum aeration rate on waste stabilization (<0.10 L/min kg waste).
Keywords: Solid waste; aerobic landfilling; leachate recirculation; aeration rate; leachate quality; MUNICIPAL SOLID-WASTE; MICROBIAL-POPULATION DYNAMICS; REFUSE DECOMPOSITION; RECIRCULATION; STABILIZATION; NITROGEN; REMOVAL; QUALITY; DESIGN; Environmental Sciences & Ecology